Meltwater Gaging Program Project No. 1, Approach Roads Tuto Area, Greenland. - ARMY ENGINEER WATERWAYS EXPERIMENT STATION VICKSBURG MISS (1963)
Measurements of meltwater flow from the ice and snow cover were made at various gaging stations in the vicinity of the Ramp, Transverse, and Access Roads near Camp TUTO, Greenland, during the summer of 1958. The purpose of these measurements was to determine the amount of meltwater flow in the vicinity of the roads. Measurements were confined chiefly to total runoff from each of two areas, although an effort was made to measure the runoff from secondary meltwater streams immediately to the north of the Ramp Road. The maximum total flow from both areas under observation was about 120 cfs and was observed at 1630 hours on 2 August. Flow was slightly in excess of 100 cfs on 12 July at 1400 hours. Runoff was affected by temperature, which in turn was affected by cloud cover, wind velocity, and elevation of observation points. Procedures for obtaining better meltwater flow data in the future are outlined.